La procreazione medicalmente assistita. Prospettiva di bilanciamento dei diritti nell’esperienza argentina (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
Both the legislative choices through which values of political, economic and bioethical values are expressed, and the jurisprudential choices, which is to say, the assessment, evaluation and legal qualification of a fact, act as a barometer of the fundamental institutional direction of a given system and its ability to cope with the accelerating evolution of science and technology and, consequently, the resulting changes in society. The issue of the law n. 26.862/2013 and of the implementing decree n. 956/2013, as well as the work of presiding judge with regard to protection, constitute the pressing response that the Argentine legal system has given to the phenomenon of medically-assisted reproduction.
Keywords: Argentina; biolaw; medically assisted procreation; balancing of rights; family autonomy